2018
DOI: 10.3390/mti2030045
|View full text |Cite
|
Sign up to set email alerts
|

EyeSpot: Leveraging Gaze to Protect Private Text Content on Mobile Devices from Shoulder Surfing

Abstract: As mobile devices allow access to an increasing amount of private data, using them in public can potentially leak sensitive information through shoulder surfing. This includes personal private data (e.g., in chat conversations) and business-related content (e.g., in emails). Leaking the former might infringe on users’ privacy, while leaking the latter is considered a breach of the EU’s General Data Protection Regulation as of May 2018. This creates a need for systems that protect sensitive data in public. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…Similar systems, like EyeSpot [77] and Private Reader [125], were proposed for privacy protection on mobile devices. In EyeSpot [77], the content that the user is gazing at is visible to them, while the rest is masked either by a black filter overlay, a crystallized mask, or fake content.…”
Section: Active Visual Privacy Protectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar systems, like EyeSpot [77] and Private Reader [125], were proposed for privacy protection on mobile devices. In EyeSpot [77], the content that the user is gazing at is visible to them, while the rest is masked either by a black filter overlay, a crystallized mask, or fake content.…”
Section: Active Visual Privacy Protectionmentioning
confidence: 99%
“…Similar systems, like EyeSpot [77] and Private Reader [125], were proposed for privacy protection on mobile devices. In EyeSpot [77], the content that the user is gazing at is visible to them, while the rest is masked either by a black filter overlay, a crystallized mask, or fake content. In the usability analysis of the different filter types, the authors found that the size of the visible spot impacts the reading speed significantly, and that the crystallized filter is more usable compared to the blackout one and fake text in terms of reading speed.…”
Section: Active Visual Privacy Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eiband et al distorted text messages using the user's handwriting, making it difficult for observers to read but not for legitmate users [5]. In EyeSpot [17], the phone's screen is distorted when texting or writing emails except for the area the user is gazing at. Crystallized masks were favored over blackout masks in EyeSpot because they maintained some contextual information (e.g., the user could still see who the last person to send a text message was), while still providing a relative protection from shoulder surfing.…”
Section: Security and Privacy Protection Through Obfuscationmentioning
confidence: 99%
“…Prior work experimented with a variety of filters to obfuscate content. The most promising ones were crystallize [17,28], mosaic (aka pixelate) [28], and Oil Paint [10,28]. The latter was shown in multiple works to be limited in terms of observation resistance [10,28].…”
Section: Designing the Filtersmentioning
confidence: 99%